PERANCANGAN PROGRAM PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB PADA SMK CAKRAWALA BOJONGGEDE BOGOR - Taupiqurahman Taupiqurahman; Helina Apriyani; Enok Tuti Alawiah; Lydia Salvina Helling (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
New Student Admission Data Management (PPDB) Cakrawala Bojonggede Vocational School Bogor is currently still using a manual system in which prospective students are required to come directly to school and meet face to face with employees to register new students. The use of a manual system that has been implemented has not been effective for the PPDB committee, especially for parents who are busy and want to enroll their children in vocational level schools such as the Cakrawala Bojonggede Vocational School in Bogor. Student acceptance website not only acts as a media of information but also to expand the area of educational development in order to reach registrants who are in the distance to get information about this school and visitors will get information on school activities without having to come directly to the school so that it makes it easier for prospective registrants or committees. The new online student acceptance website is created with the waterfall development method, and uses the PHP Codeigniter Programming Language and MySQL, so that the site display becomes more interactive, and makes it easy for servers to process data and new information quickly on the acceptance of new students.